2014
DOI: 10.1074/jbc.m113.533448
|View full text |Cite
|
Sign up to set email alerts
|

Self-renewal and Differentiation of Muscle Satellite Cells Are Regulated by the Fas-associated Death Domain

Abstract: Background:The balance between self-renewal and differentiation in muscle stem cells is critical for tissue homeostasis. Results: Fas-associated death domain (FADD) phosphorylation mutation regulates muscle satellite cell cycle progression, inhibits muscle stem cell differentiation, and promotes muscle stem cell self-renewal. Conclusion: FADD regulates muscle stem cell fate decisions. Significance: The characterization of proteins involved in fate decisions in muscle stem cells is crucial for muscle stem cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…Knockdown of FADD impairs pancreatic cancer cell proliferation, suggesting that FADD is required for cell proliferation in the context of cancer. It has been shown that FADD translocates into the nucleus during mitosis to promote cell cycle progression, implying that FADD has apoptotic and non-apoptotic roles depending upon its cellular localization (26,27). Its nuclear localization promotes cell cycle progression and simultaneously deprives proliferative cells of apoptotic stimuli (18).…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of FADD impairs pancreatic cancer cell proliferation, suggesting that FADD is required for cell proliferation in the context of cancer. It has been shown that FADD translocates into the nucleus during mitosis to promote cell cycle progression, implying that FADD has apoptotic and non-apoptotic roles depending upon its cellular localization (26,27). Its nuclear localization promotes cell cycle progression and simultaneously deprives proliferative cells of apoptotic stimuli (18).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that Fasassociated death domain (FADD) phosphorylation regulates conventional PKC (cPKC) signaling termination and cell migration [Cheng et al, 2012]. Moreover, we have also established the role of FADD phosphorylation in muscle stem cell self-renewal and commitment, which occurs mainly through cPKC-mediated Notch signaling [Cheng et al, 2014]. How cPKC mediates FADD-induced Notch signaling remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies indicated that skeletal muscles containing FADD-D exhibited a reduced myofiber size [Cheng et al, 2014]. Here, we wanted to establish whether FADD-D affected the regeneration capacity of muscles by monitoring freeze-injured TA muscle regeneration.…”
Section: Fadd-d Impairs Muscle Regenerationmentioning
confidence: 99%
See 2 more Smart Citations